Dilema Demokrasi Elektoral - I Nyoman Wiratmaja (Bali Membangun Bali: Jurnal Bappeda Litbang, 2018)
The practice of democracy is not the same as as its theory. People's sovereignty is often derailed by power-hungry political elites. Even though people in the Reform era are no longer expected to only play a limited role or merely as a giver or renew political legitimacy or as mere objects of political activity. It is worried because the practice of electoral democracy is felt further away from the spirit of democratic principles. There is still widespread behavior that justifies any means that is contrary to the values and principles of democracy, such as: politicization of SARA (suku, agama, ras, antargolongan) or politics of identity, criminalization of political opponents, dissemination of hoaxes, hate speeches, and intimidation, unneutral state apparatus, or election organizers, practices of money politics, sound auction and bribery, document forgery and manipulation of operating procedures. As a result, elected leaders often do not serve the people. All policies taken are often biased in the interests of the ruling elite or the interests of investors, and tend to be very minimal even without involving the people. In the future bad practices should not be continued and should be replaced by a shared commitment to establish substantial democracy by upholding law and justice. Stop the electoral democracy is only a lip-service of a five-year democratic party and must have a real contribution to the improvement of the nation. Electoral democracy must be an arena of healthy competition to get someone who is qualified and able to be a leader in an effort to realize common goals of just prosperity. If it fails to uphold a substantial democracy in everyday political life, then it does not only mean the castration of people's sovereignty or the failure of democracy alone, but the destruction of the Republic of Indonesia will be at stake.